Comparative metabolomic profiling of Lupinus albus and L. angustifolius harvest residues: exploring chemical diversity and valorization potential - Halime, Salma; Renaut, Jenny; Zimmer, Stéphanie; Heidt, Hanna; Jacquard, Cédric; Sergeant, Kjell (Frontiers in Plant Science, 2025)
Lupin species are a rich source of bioactive compounds with diverse industrial applications, yet their harvest residues remain underutilized. This study investigates the metabolomic composition of the harvest residues of different Lupinus albus and L. angustifolius varieties to explore species-specific biochemical differences and valorization potential. Methanolic extracts from the harvest residues were analyzed using UHPLC-MS/MS, leading to the tentative identification of 181 compounds, with saponins and flavonoids identified as the predominant metabolite classes. The data reveal distinct metabolic profiles: L. albus is characterized by higher levels of isoflavonoids (luteone), flavonols (isorhamnetin), and flavanones (naringenin), which were detected as free aglycones, glycosylated derivatives, and, for some compounds, as malonylated glycosides, which correlate with a higher antioxidant capacity. In contrast, extracts from L. angustifolius contain higher amounts of saponins, particularly soyasaponins B, E, A, and DDMP, as well as flavones (chrysoeriol and derivatives) and isoflavones (genistein and wighteone and its derivatives). Correlation analysis confirmed that a positive relationship exists between flavonoids and antioxidant activity, while saponins showed a negative correlation with antioxidant potential. This study highlights the distinct valorization opportunities of Lupinus residues: L. albus, rich in antioxidants and defense-related metabolites, holds promise for nutraceutical, pharmaceutical, and functional food applications as well as plant protection strategies. In contrast, L. angustifolius, with its high saponin content, has potential for biopesticides and antimicrobial agents. This study underscores the sustainability potential of Lupinus harvest residues as a renewable resource, supporting the upcycling of agricultural byproducts into high-value bioactive products.